A machine learning approach to predict young voter enthusiasm based on non-political factors - Rahman, Md. Nowroz Junaed; Pantho, Md. Humaun Kabir; Fuad, Nafis (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.